Stone column-supported embankments on soft soils: Three-dimensional analysis through the finite element method - Daniela Marques (2018)
In this study, the three-dimensional behavior of a stone column-supported embankment over a soft soil is analyzed using a computer code based on the finite element method. The computer code incorporates the Biot consolidation theory (fully coupled formulation of the flow and equilibrium equations) with soil constitutive relations simulated by the p-q-theta critical state model. Special emphasis is given to the analysis, during and after the construction period, of the excess pore pressures, settlements, horizontal displacements, effective stresses, stress levels, arching effect and stress concentration ratio for each column and its variation in depth. To study the overall effect of using the stone column technique, comparisons between the embankment with stone columns (three-dimensional analysis) and the embankment without stone columns (two-dimensional analysis) are also included. Several overall conclusions are put forward.